Determining Bakrie Telecom’s Business Strategy to boost the Revenue from Internet Data Business - Prajunianto, Prajunianto; Titus, Amol (The Indonesian Journal of Business Administration, 2013)
The study is aim to explore & analyze business model and business strategy for Bakrie Telecom (BTEL) in order to increase the revenue from internet data business. Trend of internet/telecommunication such as the use of smartphone (Android, IPhone, and BlackBerry) are giving significant revenue for operator. But total revenue earned by Bakrie Telecom, not quite able to offset current funds out. Issues facing Bakrie Telecom in internet data business can be overcome by applying a Business Model Canvas, which has nine factors that include improvements in Customer/Client, Brand Development, campaign activities to increase product awareness, product delivery by the supplier, resources development, budget/fees management, and which revenues to be gained. This research will get excellent result if capable of forming Canvas business model measured its success by applying Diamond business strategy in Bakrie Telecom. Those strategy is expected to increase corporate earnings especially from internet data business and able to earn internet market widespread in Indonesia. The recommendation to implement business model and business strategy are began by providing employees upgrading/training skills, improvements in terms of finances, expansion and infrastructure’s development and build the programs that can make customers interested in using internet products of Bakrie Telecom. Keywords: internet data business, canvas business model, diamond business strategy.